EVALUASI KERAGAAN USAHA PERKEBUNAN KELAPA SAWIT RAKYAT POLA PLASMA DALAM MEMENUHI STANDARISASI SERTIFIKASI RSPO DI KECAMATAN UKUI KABUPATEN PELALAWAN - Rangkuti, Indra Haryati; Hutabarat, Sakti; Rifai, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Highest productivity and cheapest price among vegetable oils has motivated manufacturers to use palm oil as principle ingredient in their products. While there are various derivative products of palm oil, demand for palm oil increase significantly. In line with higher price of oil palm fruits, the growers respond with land expansion to meet the demand of palm oil. However, massive expansion of oil palm plantations has generated various negative social and  environment impacts including deforestation, biodiversity loss, forest fires, and social conflicts. These issues have motivated private international organizations to mitigate the effects of land expansion by establishing the Roundtable on Sustainable Palm Oil (RSPO) certification. All growers and stakeholders have to comply with the RSPO standard to be included in the palm oil supply chain. The smallholders face the most challenging effort to meet the standard and to obtain the RSPO certificate. The objective of this study is to evaluate the performance of scheme smallholders and to assess their compliance to the standard of RSPO. Data were collected through a survey on 70 sample from 224 members of the population. The data were analysed using farm business analysis and assessment on the application of RSPO Principles and Criteria. The result shows that the average farm income from oil palm plantation is Rp 16.443.449,- per year/ha or Rp 1.370.287,- per month/ha. The group farmer have comply to more than 100% of  the RSPO standard. Keywords: RSPO certification, smallhoders performance, scheme smallholders, farm income